Donner une voix aux Inuit urbains : « Photovoice » comme une pratique de multilittératie dans la construction d’identité et de savoirs transfrontaliers - BUDACH, Gabriele (2011)
peer reviewed This paper reports on a collaborative, action-based research project exploring multimodal literacy practices among urban Inuit in Ottawa. Working in the context of the family literacy program of the Ottawa Inuit Children’s centre, we examine two ‘Photovoice’ activities conducted by Inuit children, youth, and adults in 2009 and 2010. The goals of this examination are twofold: 1) to explore Photovoice as a multimodal literacy explore, reflect upon, and represent aspects of urban Inuit identity and experiences; and 2) to situate Photovoice methodologically and theoretically in the realm of ‘New Literacy Studies’, which sees literacy as a social and cultural practice, rather than a set of discrete linguistic skills to be taught, learnt, and acquired. In this way, Photovoice, drawing on the visual, oral, and scriptural modes, is seen as an ideal type of literacy activity in community-based educative contexts, such as urban Inuit in Ottawa, with wider application across contexts.